Peningkatan Keterampilan Penanganan Pasien Gawat Darurat Melalui Pelatihan Basic Trauma Cardic Life Support (BTCLS) - Solehudin, Solehudin; Kurniawan, Imam; Firdaus, Muhammad Iqbal; Syabanasyah, Inas (Asosiasi Guru dan Dosen Seluruh Indonesia, 2024)
Skills in handling emergency patients, especially trauma and cardiovascular emergencies, are important competencies for health workers. Basic Trauma Cardiac Life Support (BTCLS) training is designed to improve the knowledge, skills, and readiness of health workers in dealing with critical situations. This study aims to evaluate the impact of BTCLS training on the competence of nurses at the National Search and Rescue Agency (BNPP) in handling emergencies. The method used was a six-day training, which included providing theory and practice. The theoretical material included systematic emergency management, while practice included resuscitation simulation, initial assessment, airway management, triage, and patient evacuation. Evaluation was carried out through pre-test and post-test to measure the knowledge and skills of the participants. The results showed a significant increase in the average knowledge score, from 45.5 (pre-test) to 85.5 (post-test), with an increase of 87.91%. The participants' skills reached an average of 85, indicating a high level of competence in accordance with training standards. This increase reflects the effectiveness of the training method in providing in-depth theoretical and practical understanding. Conclusion, BTCLS training has made a major contribution to improving the competence of health workers, especially BNPP nurses, in dealing with emergency situations. This program equips participants with the knowledge, skills, and confidence to handle critical cases effectively. Suggestion, BTCLS training needs to be held periodically with material updates according to technological developments and international standards to maintain the quality of health worker competence.